2007
DOI: 10.1152/ajprenal.00310.2007
|View full text |Cite
|
Sign up to set email alerts
|

Urinary matrix metalloproteinases reflect renal damage in anti-neutrophil cytoplasm autoantibody-associated vasculitis

Abstract: Sanders J-S, Huitema MG, Hanemaaijer R, van Goor H, Kallenberg CG, Stegeman CA. Urinary matrix metalloproteinases reflect renal damage in anti-neutrophil cytoplasm autoantibody-associated vasculitis. Am J Physiol Renal Physiol 293: F1927-F1934, 2007. First published September 26, 2007; doi:10.1152/ajprenal.00310.2007.-Renal expression of MMP-2, -9, and tissue inhibitor of MMP-1 (TIMP-1) correlates with histological disease activity in anti-neutrophil cytoplasm autoantibody (ANCA)-associated vasculitis (AAV). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…Serum, ethylenediaminetetraacetic acid plasma, and urine samples (N 5 26-38, depending on sample matrix) were obtained from patients with aHUS at baseline, before eculizumab treatment, and at visits 3 (weeks 1-3), 6 (weeks 4-6), 12 (weeks 12-17), 17 (weeks 26-33), 18 (weeks [38][39][40][41][42], and 19 (weeks 49-54) during eculizumab treatment. For simplicity, visit 17 is referred to as week 26 and visit 19 as week 52 of treatment.…”
Section: Biological Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum, ethylenediaminetetraacetic acid plasma, and urine samples (N 5 26-38, depending on sample matrix) were obtained from patients with aHUS at baseline, before eculizumab treatment, and at visits 3 (weeks 1-3), 6 (weeks 4-6), 12 (weeks 12-17), 17 (weeks 26-33), 18 (weeks [38][39][40][41][42], and 19 (weeks 49-54) during eculizumab treatment. For simplicity, visit 17 is referred to as week 26 and visit 19 as week 52 of treatment.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Baseline plasma F112 and D-dimer levels were also 6-and 10-fold higher than levels observed in HV in more than 94% of patients, indicating thrombin generation and fibrinolysis (Table 2). At baseline, 69% to 83% of patients with aHUS also showed significantly elevated levels of candidate renal injury biomarkers associated with acute kidney injury, ischemic injury, and nephrotoxicity in rodent models and human disease, including those associated with proximal tubular injury (U-cystatin-C, 38,[53][54][55] clusterin, 38,58,59 and b2-M 38,60 ), interstitial injury (TIMP-1 40,56 ), and deteriorating renal function (U-L-FABP-1 39,57 ); levels of these markers were 9-to 48-fold higher than levels measured in HV (Table 2).…”
Section: Biomarker Levels At Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…Kanno and colleagues 12 showed that levels of urinary sediment podocalyxin are elevated in children with cellular crescents. Levels of urinary macrophage migration inhibitory factor and matrix metalloproteinase activity are reportedly higher in patients with crescentic GN and ANCA-associated GN than in healthy controls, 13,14 but the levels are not significantly higher than in patients with other glomerular diseases. By contrast, urinary FSP1 levels strongly correlated with the percentage of glomeruli showing cellular or fibrocellular crescent formation in patients with crescent formation, irrespective of the specific glomerular disease (Supplemental Figure 3).…”
mentioning
confidence: 93%
“…Patients with various forms of glomerulonephritis including focal segmental glomerulosclerosis, minimal change disease, human immunodeficiency-associated nephropathy and antineutrophil cytoplasmatic antibody-associated vasculitis each had distinct expression of gelatinases [169-174]. Plasma concentrations of MMP-2, MMP-9, and TIMP-1 are remarkably changed in patients with primary glomerulonephritis including IgA nephropathy, membranous glomerulonephritis, minimal change nephrotic disease, and segmental glomerular sclerosis [169, 171].…”
Section: Gelatinases (Mmp-2 Mmp-9)mentioning
confidence: 99%